A comparative study on risk management based on the compliance of financial institutions with the Agri-Agra Credit Law (RA10000) in Pandi, Bulacan - Calamiong, Yna Marie; Pineda, Jose Miguel
This study explored risk management practices of five(5) financial institutions in Pandi, Bulacan; and related it with the implementation of the RA 10000, the Act Providing for an Agriculture and Agrarian Reform Credit and financing System Through Banking Institutions. The paper aimed to recognize sustainable risk management approaches of credit institutions in the area of Pandi, Bulacan. All financial institutions identified the unpredictability of income as the major agricultural risk the credit sector face in Pandi; while familiarity with farmers coupled with a detailed appraisal of loan clients was highlighted by banks and cooperatives alike as the primary risk management technique. Findings show that all financial institutions attempt to comply with the law by extending loans to agriculture in Pandi. However, when comparing ration of lending to agri-agra related activities to total loanable funds, the study found that attempts to fund agriculture are insufficient enough to meet the credit quota of twenty-five percent (25%), In spite of the credit quota, banks still allocate loans according to what is best for them. This is the reason why the researchers aimed to highlight risk management as an excellent tool in mitigating risk in agriculture-- that may also help in improving compliance to law.